2023
DOI: 10.1038/s41598-023-39889-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 13C isotope-labeled allelochemicals on the growth of the invasive plant Alternanthera philoxeroides

Zexun Hua,
Qingsong Xie,
Yue Li
et al.

Abstract: The secondary metabolites of indigenous plants have significant allelopathic inhibitory effects on the growth and development of invasive alien plants. Methyl palmitate (MP) and methyl linolenate (ML) were used as exogenous allelopathic substances. The research investigated the differences of inhibitory effects of MP and ML on the growth of seedlings of Alternantheraphiloxeroides, and calculated their morphological characteristics, biomass, physiological indicators and the response index (RI). The synthetical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Allelopathy primarily influences seed germination and seedling growth, as documented in the literature 21 , 22 . It is widely reported that allelopathic interactions can result in "low promotion and high inhibition" effects on seed germination of recipient plants 23 , 24 , although some studies have reported exclusively inhibitory outcomes 25 – 28 . In our study, the aqueous extract of T. kanedae markedly suppressed the germination of O. japonicus , T. mongolicum , and V. philippica seeds, with the degree of inhibition intensifying at higher concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Allelopathy primarily influences seed germination and seedling growth, as documented in the literature 21 , 22 . It is widely reported that allelopathic interactions can result in "low promotion and high inhibition" effects on seed germination of recipient plants 23 , 24 , although some studies have reported exclusively inhibitory outcomes 25 – 28 . In our study, the aqueous extract of T. kanedae markedly suppressed the germination of O. japonicus , T. mongolicum , and V. philippica seeds, with the degree of inhibition intensifying at higher concentrations.…”
Section: Discussionmentioning
confidence: 99%